Research on performance evaluation of green supply chain of automobile enterprises under the background of carbon peak and carbon neutralization. (November 2021) - Jin, Baohui
Abstract: Due to the increasing awareness of global warming and climate change, performance evaluation based on green supply chain management has become a key issue in recent industrial implementation, and carbon management is one of the important branches. According to the needs of China's carbon peak and carbon neutralization construction objectives, this paper improves the enterprise evaluation index system of green supply chain management of China's automobile enterprises, and selects 21 indexes from four dimensions: green procurement and supplier management, green production, green consumption and green recycling, carbon peak and carbon neutralization, highlighting the impact of carbon emission. Through the investigation of experts and the public, this paper determines the weight of the evaluation dimension and index system, as well as the use criteria of the performance evaluation index system. The optimized green supply chain performance evaluation system of automobile enterprises considering the objectives of carbon peak and carbon neutralization highlights the needs of green and low-carbon development, and can better guide the healthy development of automobile enterprises in China.